Rwanda, les collines parlent - Bellefroid, Bernard (Belgium : Derives, 2005)
Eleven years after the genocide in Rwanda, this film follows the survivors and torturers before and after the first Gacaca tribunals. Obede is accused of killing a child and is asking for forgiveness; Gahutu, has no regrets; François who was ordered to kill his own brother in order to survive, is trying to reconcile with is sister-in-law. The realities of reconciliation in post-genocide Rwanda.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films